Analisis Manajemen Sumber Daya Manusia Sekolah Dasar di Era Transformasi Digital - Syarifa Mawaddah Al Idrus; Ni Luh Tri Dewi Damayanti; Mohamad Mustari (Lembaga Einstein College (LEC), 2026)
This study aims to analyze Human Resource Management (HRM) practices at SD Negeri Karang Baru, Lombok Tengah within the broader context of digital transformation in education. This research using a qualitative approach with a case study design, the research explores how the school manages teacher planning, recruitment, placement, professional development, and performance evaluation. Data were collected through an in‑depth interview with the principal and supported by school documents. The findings indicate that the school has a human resource composition that meets academic and professional qualification standards, with HR planning conducted through needs analysis and the use of student learning data. Recruitment follows procedures established by educational authorities, while task assignments are based on teacher competencies, experience, and school needs. Professional development is carried out through teacher working groups, workshops, independent training, and the use of digital learning platforms. Teacher performance evaluation is implemented systematically through assessments of core duties, additional responsibilities, and contributions to school improvement. Overall, the study highlights that adaptive and competency‑based HRM practices play a crucial role in supporting the success of digital transformation in primary education. The findings contribute to the development of more effective and responsive HRM practices in schools.